Analisis Kandungan Kimia Biji Kopi Arabika Solok berdasarkan Tingkat Kematangan yang Berbeda - Fitri Yuwita; Ulfah Anis; Damres Uker (Jurnal Teknologi Agro-Industri, 2023)
ABSTRACT The rate of increase in coffee production in Solok, especially Arabica coffee, must be accompanied by a good post-harvest period. Now the rate of increase in the area of ​​Arabica coffee production in the Solok area has not been matched by the uniformity of the quality produced. The first thing to pay attention to in maintaining quality is the maturity level the coffee beans harvest. The purpose of this study was to determine the characteristics of the chemical content of Solok Arabica coffee beans with two different maturity levels. The material used in the study was Arabica Solok coffee beans harvested directly from the farmers' gardens. Coffee beans are picked at two different maturity levels, namely ripe and overripe Arabica coffee beans. The method used is descriptive analytics to determine the chemical properties of coffee with two maturity levels. The results showed that the level of maturity affected chemical compounds such as caffeine, protein, and fat in Solok Arabica coffee beans. Caffeine content at ripe maturity is 1.56% and increases at overripe to 2.38%. Protein content at ripe maturity is 13.35%, which increases at overripe to 13.54%. The ripe fat content, which was 13.06%, decreased to 11.70%. Keywords: Arabica Coffee, Chemical Content, Level of Maturity   ABSTRAK Laju peningkatan produksi kopi di Solok, khususnya kopi arabika harus diiringi dengan pasca panen yang baik. Saat ini laju peningkatan area produksi kopi arabika di daerah Solok belum diimbangi dengan keseragaman mutu yang dihasilkan. Hal pertama yang harus diperhatikan untuk menjaga mutu adalah tingkat kematangan dari panen biji kopi. Penelitian ini bertujuan mengetahui karakteristik kandungan kimia dari biji kopi arabika Solok dengan dua tingkat kematangan yang berbeda. Bahan yang digunakan pada penelitian adalah biji kopi Arabika Solok yang dipanen langsung dari kebun petani. Biji kopi dipetik dengan dua tingkat kematangan yang berbeda yaitu biji kopi arabika masak sempurna (ripe) dan kelewat matang (overripe). Metode yang digunakan yaitu deskriptif analitik untuk mengetahui sifat kimia kopi dengan dua tingkat kematangan. Hasil penelitian menunjukkan tingkat kematangan mempengaruhi kandungan kimia seperti kafein, protein, dan lemak pada biji kopi arabika Solok. Kadar kafein pada kematangan ripe 1,56%, meningkat pada overripe menjadi 2,38%. Kadar protein pada kematangan ripe 13.35 %, meningkat pada overripe menjadi 13.54 %. Kadar lemak ripe yaitu 13.06% mengalami penurunan menjadi 11.70 %. Kata kunci : Kopi Arabika, Kandungan Kimia, Tingkat Kematangan